Vegetation of the Sierra Madre Occidental, Mexico: a synthesis - González-Elizondo, M. Socorro; González-Elizondo, Martha; Tena-Flores, J. A.; Ruacho-González, Lizeth; López-Enríquez, I. Lorena (Instituto de Ecología, A.C., 2012)
The Sierra Madre Occidental (SMO) is the largest mountain range in Mexico, extending along more than 1200 km from northeastern Sonora (30°35' N) ca at the US-Mexico border to northern Jalisco (21°00' N) on western Mexico. It includes part of the states of Sonora, Chihuahua, Durango, Zacatecas, as well as small areas of Sinaloa, Nayarit, Jalisco, and Aguascalientes. Of major ecological and economical importance, with a high biological and cultural diversity, this cordilleran complex is not yet well known. For this area, information about the different vegetation types, their elevational ranges, and the climates influencing them, is presented, as is a map showing the geographical distribution of the vegetation types. The area encompasses a confluence of Madrean, Xerophytic Madrean, and Tropical ecosystems. The Madrean region, with temperate and semi-cold climates, includes five vegetation types: pine forest, mixed-conifer forest, pine-oak forest, oak forest and temperate mesophytic forest, as well as communities of primary and secondary chaparral and montane meadow vegetation. The Xerophytic Madrean region, at foothills and eastern branches of the cordillera, has temperate or semi-cold dry climates and a vegetation of oak or pine-oak woodland and evergreen Juniperscrub, with transitions toward the grassland and xerophytic scrub areas of the Mexican high plateau or even to the subtropical scrub at the southern area of the Madrean Archipelago subregion. The Tropical region, entering the SMO through the deep canyons on the western flanks, has warm, semi-warm, and dry-warm climates and a prevalence of tropical deciduous forest and subtropical scrub, with small areas of tropical semideciduous forest. The high species richness of this range can be exemplified with the three physiognomically dominant genera: 24 species of Pinus (46% of the Mexican total), 54 species of Quercus (34%), and 7 species of Arbutus (100%).